Current progress of Ayurveda treatments on uterine fibroids: a comprehensive review - Karunagoda, K.P.K.R.; Perera, P.K.; Senanayake, H. (Sri Lanka Journal of Indigenous Medicine (SLJIM), University of Colombo, 2020)
This study aimed to provide comprehensive review on current progress of treating uterine fibroids with Ayurveda treatments. Present review adhered to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Literature was searched in PubMed®, MEDLINE, and Web of Science® up to October 2019 with specific key words. Articles published in peer-reviewed journals written in English were included. Total 16 articles were included for present review after following the search strategies, 56.25% were case reports with zero randomized control trials. Common features identified by the trials; most of the trials based on Ayurveda treatment regimens, changes of the fibroid size was measured by ultra sonography but details on research methodology of the trials were limited. The current reviewed research works do not strongly support the effectiveness of Ayurveda treatment as a management option for uterine fibroids in scientific background, even some positive findings were observed. Therefore, there is a need of a welldesigned randomized controlled trials to prove the effect of Ayurveda interventions to control uterine fibroids and related clinical features in the future.
Keywords: Uterine fibroids; Ayurveda treatments; Comprehensive review